2020
DOI: 10.2147/bctt.s262544
|View full text |Cite
|
Sign up to set email alerts
|

<p>Do Men and Women in Saudi Arabia Have the Same Level of Awareness and Knowledge of Breast Cancer? A Cross-Sectional Study</p>

Abstract: Context: Awareness is important in combating breast cancer, as early detection (through mammograms) and prompt treatment offer the greatest chance of long-term survival. Aims: The aim of this study was to assess public knowledge of breast cancer (signs, symptoms, and risk factors) and awareness of screening programs; and compare it among men and women. Materials and Methods: A cross-sectional study was conducted among male and female residents of five of the geographic regions of Saudi Arabia from February 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…Despite the low level of knowledge, our study noted that women had a higher level of awareness than men. The results of a study conducted in Saudi Arabia were similar to our findings ( Farsi et al, 2020 ). This finding can be explained by the fact that women acknowledge breast diseases more than men, and as a result, they are more open to knowledge.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite the low level of knowledge, our study noted that women had a higher level of awareness than men. The results of a study conducted in Saudi Arabia were similar to our findings ( Farsi et al, 2020 ). This finding can be explained by the fact that women acknowledge breast diseases more than men, and as a result, they are more open to knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…Literature on male breast cancer awareness is limited. Awareness studies generally focused on male high school students ( Al-Amoudi et al, 2016 ), female teachers ( Al-Ismaili et al, 2020 ), migrant agricultural workers ( Furgurson et al, 2019 ), nursing students ( Yakar et al, 2021 ), women, and men ( Alsowiyan et al, 2020 ; Farsi et al, 2020 ), yet all these studies questioned breast cancer regardless of gender.…”
Section: Discussionmentioning
confidence: 99%
“…Saeed et al 24 in 2014 reported that only 43.1% of women in Kuwait who participated in a survey related to BC awareness had overall good knowledge of BC with regard to symptoms, risk factors, and breast examination. Al Ramadhan 25 27 reported that the general knowledge among men and women regarding BC in SA is around 60% and 50%, respectively; knowledge of breast screening practices (selfexamination, clinical examination, and mammography) is around 24% and 19%, respectively.…”
Section: Dear Editormentioning
confidence: 99%
“…Alkhawari et al 26 reported that only 7.8% of the target population of women between the age of 40 and 69 years participated in screening mammography in Kuwait between 2014 and 2019. Farsi et al 27 reported that the general knowledge among men and women regarding BC in SA is around 60% and 50%, respectively; knowledge of breast screening practices (self-examination, clinical examination, and mammography) is around 24% and 19%, respectively.…”
mentioning
confidence: 99%
“…Abu Awad et al ( 2020) investigated Emirati and non-Emirati women's attitudes towards BC screening and recommended using social media and WhatsApp intensively to distribute information. Farsi, Al-Wassia, and Merdad (2020) found that BC awareness campaigns in Saudi Arabia, directed at either men or women, remain overly critical in increasing knowledge and changing behaviour regarding the early detection of BC. In Jordan, the message content and the stimuli of these campaigns have the most significant role in encouraging women to early BC examination (Azzam & Al Hawamdeh 2019).…”
Section: Bc Media Awareness Campaigns In the Arab Regionmentioning
confidence: 99%